The influence of environmental factors on bone tissue engineering1. Issue 4 (19th November 2012) - Szpalski, Caroline; Sagebin, Fabio; Barbaro, Marissa; Warren, Stephen M.
Abstract: Bone repair and regeneration are dynamic processes that involve a complex interplay between the substrate, local and systemic cells, and the milieu. Although each constituent plays an integral role in faithfully recreating the skeleton, investigators have long focused their efforts on scaffold materials and design, cytokine and hormone administration, and cell‐based therapies. Only recently have the intangible aspects of the milieu received their due attention. In this review, we highlight the important influence of environmental factors on bone tissue engineering. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2013.